Ploidy and fruit trait variation in oil-tea Camellia: Implications for ploidy breeding - Yanmin Li; Liangjing Yin; Xianyu He; Cenlong Hu; Ronghua Wu; Qian Long; Shixin Xiao; Deyi Yuan (Journal of Integrative Agriculture, 2024)
Plant polyploidy often occurs in conjunction with higher yield and superior quality. Therefore, obtaining polyploid germplasms is a significant part of breeding. The oil-tea Camellia tree is an important native woody plant that produces high-quality edible oil and includes many species of Camellia with different ploidies. However, whether higher ploidy levels in oil-tea Camellia trees are related to better traits remains unclear. In this study, the ploidy levels of 30 different oil-tea Camellia strains in three different species in the Sect. Paracamellia were determined by flow cytometry and chromosome preparation, and the phenotypic characteristics and fatty acid compositions of the fruits were examined by field observations and laboratory analyses. The correlations between the ploidy level of oil-tea Camellia and the main traits of the fruit were investigated. Our results showed that 10 Camellia lanceoleosa strains were diploid, 10 Camellia meiocarpa strains were tetraploid and 10 Camellia oleifera strains were hexaploid. Hexaploid C. oleifera had larger fruit size and weight, more seeds per fruit, greater seed weight per fruit, higher oil content and greater yield per crown width than tetraploid C. meiocarpa and diploid C. lanceoleosa, but their fruit peel thickness and fresh seed rate were significantly lower, and these traits were significantly correlated with ploidy level. In addition, in terms of fatty acid composition, hexaploid C. oleifera had a higher oleic acid content than tetraploid C. meiocarpa and diploid C. lanceoleosa, but their linoleic acid, linolenic acid and arachidonic acid contents were lower. The contents of palmitic acid, stearic acid and total unsaturated fatty acids were not significantly correlated with ploidy level. In conclusion, certain correlations exist between the main characteristics of oil-tea Camellia fruit and the ploidy level, and increasing the ploidy level led to an increase in fruit yield with no effect on oil composition. The discovery of variations in the main characteristics of oil-tea Camellia fruit with different ploidies will facilitate germplasm innovation and lay a foundation for ploidy breeding and mechanistic research on fruit traits.